1996
DOI: 10.1074/jbc.271.24.14533
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease Resistance and Antisense Activity of Modified Oligonucleotides Targeted to Ha-

Abstract: We have previously described structure-activity studies on a 17-mer uniform phosphorothioate antisense sequence targeted to human Ha-ras. In an effort to further improve the pharmacological properties of antisense oligonucleotides, structure-activity studies on this 17-mer sequence were expanded to examine both the effects of replacing phosphorothioate backbone linkages with phosphodiester linkages and the effects of incorporating various 2-sugar modifications into phosphorothioate and phosphodiester oligonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 28 publications
5
110
0
Order By: Relevance
“…designed gapmers with CAG repeat sequences containing LNA and MOE modifications, both of which are resistant to nucleases and have increased affinity to RNA (24,25). The gapmers were sufficient to knockdown the mutant CUG transcripts both in cell culture and DM1 mice, providing proof of principle that the RNase H pathway may be exploited for use in DM1 therapy.…”
Section: Discussionmentioning
confidence: 95%
“…designed gapmers with CAG repeat sequences containing LNA and MOE modifications, both of which are resistant to nucleases and have increased affinity to RNA (24,25). The gapmers were sufficient to knockdown the mutant CUG transcripts both in cell culture and DM1 mice, providing proof of principle that the RNase H pathway may be exploited for use in DM1 therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, previous reports mention the necessity for chemical modification of ODNs in order to increase their resistance to nucleases, their intracellular concentration and duration and thus, their pharmacological efficacy. 43 To reduce the risk of degradation we used phosphorothioate-modified ODNs (at both 3′ and 5′ ends). We observed that when incubated alone with complete culture medium (RPMI 1640 containing 10% FCS), a slow rate of degradation of phosphorothioate-modified ODNs occurred within 72 h; however, nuclease sensitivity was totally prevented for at least 72 hours in the presence of MPG (Figure 4), a chimerical peptide that we used to vectorize ODNs into the nucleus and that has been previously reported to preserve ss-or ds-ODNs integrity.…”
Section: Discussionmentioning
confidence: 99%
“…2Ј-O-Alkyl-RNA, a second-generation class of oligonucleotide, binds complementary sequences with high affinity relative to analogous DNA or RNA oligonucleotides (26)(27)(28)(29)(30). The clinical application of 2Ј-O-meRNA with a phosphorothioate backbone is being explored in a phase one trial directed against the R1-␣ subunit of protein kinase A in refractory solid tumors and a phase one/two trial directed against cytomegalovirus retinitis.…”
mentioning
confidence: 99%